2016
DOI: 10.1093/annonc/mdw201.15
|View full text |Cite
|
Sign up to set email alerts
|

RM-015 Clinicopathological, epidemiological and outcome of treatment of advanced gastric cancer in Egypt: single institution experience

Abstract: Introduction: Gastric cancer is the 3rd cause of cancer related deaths worldwide. In Egypt, it is 12th in position regarding incidence and cancer-related deaths. About 65% of patients present with locally advanced or metastatic disease with 5-year survival rates of 30% and 5% respectively. Several prognostic factors had been identified for gastric cancer including stage, location, pathological subtype, peritoneal deposits, and HER2-neu over-expression. In this retrospective analysis, we are aiming at identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
0
1
Order By: Relevance
“…According to the Lauren classification, we conclude a predominance of diffuse gastric cancer over the intestinal type at 25% and 19.2% respectively and this is in agreement with Elzoki et al (17) who showed that diffuse adenocarcinoma occurred in 56 patients (49.1%), intestinal adenocarcinoma in 46 (40.4%) and malignant gastric lymphoma in 12 (10.5%). This is also consistent with a Jordanian study where most of the cases were of the diffuse, signet ring type (52%, 53 cases), whereas 40% were the intestinal type (4 cases) (18) , and also with Mohamed et al (19) and Gaballah et.al (20) , two Egyptian studies where the diffuse pattern was predominant. However, this result is in discordance with some other studies done in other Arab countries which show that histologically, the intestinal type of cancer is more common than diffuse cancer in Sudan, Yemen, Jordan and Tunisia (21) (22)(23)(24) (25)(26) (27) .…”
Section: Discussionsupporting
confidence: 91%
“…According to the Lauren classification, we conclude a predominance of diffuse gastric cancer over the intestinal type at 25% and 19.2% respectively and this is in agreement with Elzoki et al (17) who showed that diffuse adenocarcinoma occurred in 56 patients (49.1%), intestinal adenocarcinoma in 46 (40.4%) and malignant gastric lymphoma in 12 (10.5%). This is also consistent with a Jordanian study where most of the cases were of the diffuse, signet ring type (52%, 53 cases), whereas 40% were the intestinal type (4 cases) (18) , and also with Mohamed et al (19) and Gaballah et.al (20) , two Egyptian studies where the diffuse pattern was predominant. However, this result is in discordance with some other studies done in other Arab countries which show that histologically, the intestinal type of cancer is more common than diffuse cancer in Sudan, Yemen, Jordan and Tunisia (21) (22)(23)(24) (25)(26) (27) .…”
Section: Discussionsupporting
confidence: 91%
“…In the present work, male predominance was reported which is similar to the worldwide trend (2:1) [ 22 ], as 73.5% of gastric lesions belonged to males compared to 26% belonged to females, with incidence 2.8:1. A percentage lower than ours reported by Gaballah et al, [ 23 ] and Darwish et al, [ 24 ] who reported male to female ratio of 1.2:1 and 1.3: 1 respectively.…”
Section: Discussioncontrasting
confidence: 76%